Integrating SD Indicators into a BIM of a Factory Heritage Site (EAAE Annual Conference Proceedings, 2023)
The research project looks at how to integrate indicators for sustainable development into a building information model. The idea is to combine the fields of sustainability, digital construction, and renovation. The case study for the ongoing research is the listed building ‚white-hall’ which is part of a factory site and is going to be transformed into the faculty of architecture of the HEIA-FR.